An Experimental Study on the Properties of Concrete by Partial Replacement of Cement with Egg Shell Powder (ESP) and Rice Husk Ash (RHA) - Gorantla Rajkiran, Prof. H. Sudarsana Rao, Dr. Vaishali G. Ghorpade (International Journal of Advanced Science and Technology, 2020)
In the evolution of the construction industry cement concrete has played a significant role since the manufacturing of ordinary Portland cement has been started, in building many of the greatest structures in the world. But from the past few decades, researchers are putting their efforts into identifying the substitute for cement in concrete among various waste products from industrial, agricultural processing units. There is need to minimize the construction cost and the quantity of cement, as its manufacturing creates heavy air pollution. In this work, the suitability of Egg shell powder, Rice husk ash which are waste products from poultry and agricultural industries respectively as a partial replacement for cement in M30 grade concrete is attempted. The combination of these two materials with four distinct proportions as 5%, 10%, 15%, and 20% are used to replace cement by weight and the corresponding variation of strength is determined from compression, split tensile and flexural test results.